ORGANIZATIONAL AND METHODOLOGICAL WORK NECESSARY FOR THE INTRODUCTION OF INCLUSIVE EDUCATION INTO PRACTICE - Yuldashev Sodirjon Jo’rayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article examines the proposed conclusions about the problems for which the current topic is waiting for a solution to changes in the practice of inclusive education.